2017
DOI: 10.17712/nsj.2017.2.20160330
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and prognostic role of mean platelet volume in patients with first-ever acute ischemic stroke

Abstract: Objective:To investigate any possible effects of mean platelet volume (MPV) on short-term stroke prognosis and functional outcome in patients with first-ever acute ischemic stroke (FEAIS).Methods:This retrospective cross-sectional study included 798 FEAIS patients admitted to the emergency department of a tertiary care hospital in Adiyaman, Turkey between January 2013 and June 2015. The data were evaluated according to whether alive or dead, MPV levels, modified Rankin scale (MRS) scores, National Institutes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…In a retrospective study by Lok et al (27), who investigated AIS patients, MPV was found to have no predictive or prognostic value. This study also showed similar findings in CV patients, and it was concluded that MPV had no value regarding the differential diagnosis between CV and PV.…”
Section: Discussionmentioning
confidence: 95%
“…In a retrospective study by Lok et al (27), who investigated AIS patients, MPV was found to have no predictive or prognostic value. This study also showed similar findings in CV patients, and it was concluded that MPV had no value regarding the differential diagnosis between CV and PV.…”
Section: Discussionmentioning
confidence: 95%
“…Another study by Nataios et al (16) measured MPV values within the first 24 hours after the onset of stroke and found that MPV levels were not associated with stroke severity and limitation of neurological functions. Further, a retrospective study by Lok et al (17) in 2017 which 798 first time acute ischemic stroke patients participated, showed that MPV values were not associated with short-term stroke prognosis and neurological functions. Also, a study compared MPV values of 281 first-episode acute ischemic stroke and 164 first-episode hemorrhagic stroke patients and found that MPV values were high in both groups but it is not associated with the prognosis (5).…”
Section: Discussionmentioning
confidence: 96%
“…Hypertension was the most prevalent risk factor in this study with a percentage of 82. Study conducted by Lok U et al 13 and A. Muscari et al showed hypertension to be the most prevalent risk factor with a percentage of 74 and 84.7 respectively. The other common risk factors were smoking, alcohol, diabetes mellitus and dyslipidaemia.…”
Section: Risk Factors For Strokementioning
confidence: 94%